Bibliometric Study of Sodium Glucose Cotransporter 2 Inhibitors in Cardiovascular Research - Chen, Lu; Ma, Siyuan; Hu, Donghong; Lin, Hairuo; Zhu, Yingqi; Chen, Kaitong; Chen, Lin; Zheng, Cankun; Liu, Jichen; Liao, Yulin (Frontiers in Pharmacology, 2020)
Background: An increasing number of studies have shown that sodium glucose cotransporter 2 (SGLT2) inhibitors, initially used as antidiabetic agents, have cardiovascular (CV) benefits. However, few bibliometric analyses have examined this field systematically. Our study aimed to visualize the publications to determine the trends and hotspots in CV research on SGLT2 inhibitors. Methods: Publications on SGLT2 inhibitors in cardiovascular research were retrieved from the Web of Science Core Collection. Microsoft Excel 2019, VOSviewer and CiteSpace V were used to analyze and plot the references. Results: On July 3, 2020, 1509 records of CV research on SGLT2 inhibitors published from 2013-2020 were retrieved. Nearly half were authored by American scholars, and most were published in Diabetes Obesity Metabolism, Cardiovascular Diabetology, and Diabetes Therapy. The USA was the leading driving force, with a strong academic reputation in this area. Inzucchi SE published the most related articles, while Neal B was cited the most frequently. All the top 10 co-cited references were in the leading co-cited journal, The New England Journal of Medicine. “Atherosclerotic cardiovascular event” was the leading research hotspot. The keywords “cardiac metabolism”, “heart failure hospitalization”, and “heart failure with preserved ejection fraction” appeared most recently as research frontiers. Conclusion: Most studies focused on clinical trial outcomes, such as cardiovascular death and heart failure (HF) hospitalization. The mechanisms of SGLT2 inhibitors, especially those related to cardiac metabolism, may soon become hotspots and should be closely monitored.